1961
DOI: 10.1139/v61-271
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Spectra of Pyridinium Salts

Abstract: 'The vibrational spectrum of the pyridiniuln ion, CjHjI\TH+, and the N-deuterated species has been studied in several pyridinium salts. By comparison with benzene and deuterobenzene (with which the p y r i d i n i~~~n ion is isoelectronic) a fairly complete assignment has been made. The N-H bonds, which are hydrogen bonded to the anions, have stretching vibrations which show systematic variations depending on the nature of the anion. The N-H in-plane deformation vibrations show little variation while the out-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
111
0
1

Year Published

1964
1964
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 270 publications
(130 citation statements)
references
References 13 publications
18
111
0
1
Order By: Relevance
“…guishing features of protonated Fluazifop are: (1) the occurrence of a weak absorption in the N-H stretching region centered at 3065 cm -l due to the protonated pyridinic nitrogen, and (2) the shift of the v8a ring vibration from 1580 (Wilmshurt and Bernstein, 1957) to 1655 cm -1, the latter value being typical of pyridinium compounds (Cook, 1961;Farmer and Mortland, 1966).…”
Section: Resultsmentioning
confidence: 99%
“…guishing features of protonated Fluazifop are: (1) the occurrence of a weak absorption in the N-H stretching region centered at 3065 cm -l due to the protonated pyridinic nitrogen, and (2) the shift of the v8a ring vibration from 1580 (Wilmshurt and Bernstein, 1957) to 1655 cm -1, the latter value being typical of pyridinium compounds (Cook, 1961;Farmer and Mortland, 1966).…”
Section: Resultsmentioning
confidence: 99%
“…Previously published work (20) has established that the in-plane hydrogen-bending mode in pyridinium salts gives rise to an absorption band near 1240 cm-l. No splitting was observed in the HC1 salt (or others), which is in accordance with the selection rules using the details of the crystal structure determined by RCrat (21). Spinner (22) assigned a band near 1250 cin-I in the infrared spectra of the hydrochlorides of several 2-, 3-, and 4-substituted pyridines to the NH in-plane bending mode, though this assignment was not confirmed by deuterium substitution.…”
Section: Heterocyclic Nitrogen Compoz~ndsmentioning
confidence: 98%
“…These bands are assigned to the outof-plane vibration mode of C-H (BELLAMY 1955). It has been reported (COOK 1961) that the pyridinium ion shows characteristic changes in the out-of-plane C-H deformation modes on charge-transfer complex formation with anions and that the shifts are a function of the electronegativity values of the anions. KROSS et al (1956) observed a shift in the C-H out-of-plane bending vibration frequency in mono-substituted and para-substituted benzenes.…”
Section: G) Mechanisms Of Adsorptionmentioning
confidence: 92%